Qualidade de vida do idoso com doença de Alzheimer e o cuidador formal: relacionando afetividade (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Quality of life of the elderly with Alzheimer’s disease, formal caregivers and affectivity